2021
DOI: 10.1111/dth.14745
|View full text |Cite
|
Sign up to set email alerts
|

Identification of differentially expressed circular RNAs in keloid and normal skin tissue by high‐throughput sequencing

Abstract: Keloid is a kind of pathological skin scar with unclear molecular pathology. Circular RNAs (circRNAs) are involved in the occurrence and development of many diseases; however, their relationship with keloid is not well understood. To investigate the involvement of dysregulated circRNAs in keloid. Thirty-seven keloids and 37 normal skin tissues were collected, and the changes of circRNAs, microRNAs (miRNAs) and mRNAs in 3 keloids and 3 normal samples by high-throughput sequencing were detected first. Based on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 36 publications
(65 reference statements)
2
6
0
Order By: Relevance
“…Importantly, based on bioinformatics analysis and validation experiment, we identified that hsa_circ_0001320 and hsa_circ_0001924 may serve as candidate genes for VKH disease. Our results are, by and large, similar to that in keloid reported by Zhang et al ( 32 ). They show that the hsa_circ_0001320 has an aberrantly higher expression in this disease.…”
Section: Discussionsupporting
confidence: 93%
“…Importantly, based on bioinformatics analysis and validation experiment, we identified that hsa_circ_0001320 and hsa_circ_0001924 may serve as candidate genes for VKH disease. Our results are, by and large, similar to that in keloid reported by Zhang et al ( 32 ). They show that the hsa_circ_0001320 has an aberrantly higher expression in this disease.…”
Section: Discussionsupporting
confidence: 93%
“…Lv et al [ 32 ] found that circCOL5A1 released Epac1 as a competing endogenous RNA via adsorption of miR-7-5p to facilitate pathological hyperplasia of keloids. Zhang et al [ 33 ] revealed that the interaction between hsa_circ_0001320 and miR-574-5p regulates the keloid pathology. In this study, we demonstrated that hsa_circ_0057452 is overexpressed in keloids, which is consistent with previously published circRNA microarray analysis [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the non-self-controlled samples introduced various confounding factors, and long-term culture or in vitro manipulation may alter the epigenetics. Two other articles analyzed the circRNA expression of full-thickness keloid tissues and introduced the impact of epidermal tissues [20,21]. However, none of the four studies have reported the etiology of keloid patients.…”
Section: Discussionmentioning
confidence: 99%